2017
DOI: 10.1097/hmr.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the link between human resource management decisions and patient satisfaction with quality of care

Abstract: Hospital managers are advised to consider the effects of HRM decisions on patients' satisfaction with care. In particular, investments in SHRM targeted at physicians have significantly positive effects on patient satisfaction, whereas the temporary staffing of physicians and nurses should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Eighteen qualitative studies that used interviews and/or focus group studies [16–32] were identified. Other studies were quantitative [33–39] including the use of questionnaires or survey data, or used a mixed-method approach [40–44]. Other articles combined different types of primary and secondary data (key informant interviews, observations, focus groups, questionnaire/survey data, and government reports).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen qualitative studies that used interviews and/or focus group studies [16–32] were identified. Other studies were quantitative [33–39] including the use of questionnaires or survey data, or used a mixed-method approach [40–44]. Other articles combined different types of primary and secondary data (key informant interviews, observations, focus groups, questionnaire/survey data, and government reports).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that employees who perceive they are managed with positive HRM practices are likely to demonstrate improved performance and competence, which is likely to positively affect organizational outcome . Our review found that CBHRM affects the quality of health care, patient safety, and patient satisfaction . Thus, if we want to drive important organizational outcomes, a good strategy to start with is focusing on “people.”…”
Section: Resultsmentioning
confidence: 99%
“…Unquestionably, caregivers play a crucial role in social care. Inadequate human resources, both in quantity and quality, could hinder performance achievement (Ghenţa et al, 2015) or negatively impact care quality (Eaton, 2000;Oppel et al, 2017). On the other hand, improving working conditions leading to greater job satisfaction and commitment could contrib-ute to better quality and more efficient work with human resources (Cooke and Bartram, 2015).…”
Section: Introductionmentioning
confidence: 99%